ANALISIS PENGARUH KUALITAS INFORMASI DAN KUALITAS PELAYANAN WEBSITE DALAM MENINGKATKAN MINAT BELI ULANG MAHASISWA UNIVERSITAS DIPONEGORO PADA SITUS ELEVENIA.CO.ID DENGAN MENGGUNAKAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI - Ramadhan, Gear; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2017)
Indonesia is a very potential market for developing e-commerce business. Elevenia.co.id is one of the newcomer e-commerce sites in Indonesia, but based on a survey conducted by similarweb.com shows in the last six months the number of visitors elevenia.co.id site continues to experience a drastic decline, this indicates the low interest in buying to the site elevenia.co.id. This study aimed to analyze the effect of quality information and quality of service on the website to customer satisfaction in the increasing repurchase intention on Elevenia.co.id site. Variables used in this research is the quality of information and service quality as an independent variable, customer satisfaction as mediating variables and repurchase intention as the dependent variable.The sample used in this study were 147 students at the University of Diponegoro who did purchased transaction on Elevenia.co.id. Data collection method used is to questionnaires distributed by non-probability sampling technique with the kind of purposive sampling. The analytical method used is Structural Equation Modeling (SEM) were analyzed using analysis tools with AMOS 20.0 Maximum Likelihood technique.The results of SEM analysis carried out, indicate that the quality of information has a positive and significant impact on customer satisfaction and repurchase intention, meanwhile quality of service has a positive and significant impact on consumer satisfaction but has no direct influence on repurchase intention and consumer satisfaction have a positive influence and significantly to repurchase intention. Thus, to increase repurchase intention in Elevenia.co.id sites, companies must improve consumers satisfaction by providing quality information and quality of service as possible on the website